2022
DOI: 10.3390/jcm11143954
|View full text |Cite
|
Sign up to set email alerts
|

Single-Centre Retrospective Evaluation of Intraoperative Hemoadsorption in Left-Sided Acute Infective Endocarditis

Abstract: Background: Cardiac surgery in patients with infective endocarditis (IE) is still associated with high mortality and morbidity; an already present inflammation might further be aggravated due to a cardiopulmonary bypass-induced dysregulated immune response. Intraoperative hemoadsorption therapy may attenuate this septic response. Our objective was therefore to assess the efficacy of intraoperative hemoadsorption in active left-sided native- and prosthetic infective endocarditis. Methods: Consecutive high-risk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 33 publications
1
23
0
Order By: Relevance
“…Integrating the CytoSorb adsorber into the extracorporeal circulation assembly during cardiac surgery serves as the theoretical premise that cytokines induced through surgical trauma and the very application of cardiopulmonary bypass are eliminated at the time of their synthesis, thus promoting hemodynamic stability in the early postoperative phase, which was proven by the REMOVE trial [ 14 ]. In the context of infective endocarditis, hemoadsorption with CytoSorb resulted in less dependency on catecholamine therapy for patients undergoing dialysis postoperatively [ 13 , 33 , 34 ]. As mentioned above, the results of the multicenter, randomized, controlled REMOVE study (Cytokine Hemoadsorption During Cardiac Surgery Versus Standard Surgical Care for Infective Endocarditis) were published [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Integrating the CytoSorb adsorber into the extracorporeal circulation assembly during cardiac surgery serves as the theoretical premise that cytokines induced through surgical trauma and the very application of cardiopulmonary bypass are eliminated at the time of their synthesis, thus promoting hemodynamic stability in the early postoperative phase, which was proven by the REMOVE trial [ 14 ]. In the context of infective endocarditis, hemoadsorption with CytoSorb resulted in less dependency on catecholamine therapy for patients undergoing dialysis postoperatively [ 13 , 33 , 34 ]. As mentioned above, the results of the multicenter, randomized, controlled REMOVE study (Cytokine Hemoadsorption During Cardiac Surgery Versus Standard Surgical Care for Infective Endocarditis) were published [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…The poorer outcomes observed in patients undergoing cardiac surgery with confirmed culture-positive IE and S. aureus , in particular, are likely due to the frequent occurrence of postoperative sepsis resulting from the combination of a cytokine driven systemic inflammatory response (SIR) and underlying systemic infection [ 4–8 ]. Blood purification using haemoadsorption (HA) therapy is increasingly used in high-risk cardiac surgery cases, including acute IE, to modulate SIR and improve postoperative outcomes [ 9 ]. Blood purification, in addition to removal of cytokines, HA is able to remove S. aureus toxin and haemolysin from blood [ 10 ], what may make it a particularly attractive intervention for patients with confirmed S. aureus IE.…”
Section: Introductionmentioning
confidence: 99%
“…Extracorporeal haemoadsorption is a blood purification technology with confirmed adsorption capacity for cytokines, chemokines, bilirubin, myoglobin, plasma free haemoglobin, and various pharmacological agents 7–9 . Recent clinical investigations have reported reduced sepsis related mortality, less bleeding complications related to adsorption of direct acting oral anticoagulants or P2Y 12 inhibitors, and faster recovery of haemodynamics and organ function in patients undergoing complex cardiac surgeries when intraoperative haemoadsorption has been applied 8,10–13 . Similarly, our previous observational study showed that OHT recipients who were treated with haemoadsorption intraoperatively experienced significantly reduced post‐operative vasopressor requirements and favourable trends in clinical outcome 14 .…”
Section: Introductionmentioning
confidence: 75%
“…[7][8][9] Recent clinical investigations have reported reduced sepsis related mortality, less bleeding complications related to adsorption of direct acting oral anticoagulants or P2Y 12 inhibitors, and faster recovery of haemodynamics and organ function in patients undergoing complex cardiac surgeries when intraoperative haemoadsorption has been applied. 8,[10][11][12][13] Similarly, our previous observational study showed that OHT recipients who were treated with haemoadsorption intraoperatively experienced significantly reduced post-operative vasopressor requirements and favourable trends in clinical outcome. 14 While the number of randomized and observational studies for the evaluation of haemoadsorption in cardiac surgery has increased in the last 10 years, published results remain controversial regarding clarifying the clinical utility of this intervention in terms of post-operative morbidity and mortality.…”
Section: Introductionmentioning
confidence: 85%